EVALUASI KERAPATAN JARINGAN POS PENCATATAN HUJAN DI DAS KEYANG SLAHUNG TEMPURAN, PONOROGO MENGGUNAKAN METODE KAGAN-RODDA - Mar'atu Rifatil Jannah; Mahendra Andiek Maulana; Yang Ratri Savitry (Departemen Teknik Infrastruktur Sipil Institut Teknologi Sepuluh Nopember Surabaya, 2023)
The accuracy of hydrological quality and quantity data is inseparable from the importance of the hydrological postal network. The quality of data has highly effective on planning, developing, and controlling infrastructure, so the placement of rain recording posts is very important to produce the watershed produced can describe a watershed. This research uses standards from the WMO (word Meteorological Organization) and Kagan-Rodda. The results of the WMO standard produced 11 selected rain posts from 18 rain posts, while with the Kagan-Rodda method, 11 rain posts were obtained from 18 rain posts, namely Ngrayun, Pudak, Purwantoro, Bollu, Pulung, Ponorogo, Sumoro, Slahung, sawoo, Ngilo-Ilo, Sumoroto.